Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557182
|View full text |Cite
|
Sign up to set email alerts
|

MinEMail

Abstract: Email is the primary method of digital communication for most people, but the overwhelming quantity has led to a poverty of attention. Existing manual and automatic solutions that aim to save important emails from falling through the cracks have begun to address this problem, but may increase user workload, sacrifice efficiency, or fail to identify high value communications. In response, we developed MinEMail, an alert system that uses a text message (SMS) to remind and notify users of critical emails that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They demonstrated that even though work email has doubled in size over the years, personal email accounts were found to be 5 times bigger than work ones, especially for the number of unread messages. Despite this huge growth of exchanged emails, Rector and Hailpern [28] found that only 12.37% of emails are actually critical (i.e. too important to miss).…”
Section: Personal Emailmentioning
confidence: 99%
“…They demonstrated that even though work email has doubled in size over the years, personal email accounts were found to be 5 times bigger than work ones, especially for the number of unread messages. Despite this huge growth of exchanged emails, Rector and Hailpern [28] found that only 12.37% of emails are actually critical (i.e. too important to miss).…”
Section: Personal Emailmentioning
confidence: 99%
“…found that recipients still did not interpret the prices as emails' importance), indicating expected actions [2,38], etc.…”
Section: Discussionmentioning
confidence: 99%